(untitled) (Research, Society and Development, 2023)
Introduction: Hypothyroidism is a metabolic disease caused by the reduction or absence of thyroid hormones. When damaged or negatively stimulated, the thyroid gland stops producing its hormones, which results in various symptoms. The role of nutrients in maintaining the gland’s homeostasis and in controlling hypothyroidism has been widely studied, as a means of auxiliary treatment. Objectives: To identify the influence of selenium and iodine in the control of hypothyroidism. Methods: Through an integrated review, articles from the past 6 years have been found, with the purpose of searching for current scientific evidence around the subject. This review was done in six stages, and the following databases have been used: Digital Library of Theses and Dissertations from University of São Paulo; Google Scholar; LILACS; Lume Digital Repository; Capes Periodicals, National Library of Medicine (PubMed) and SciELO. The determination of the final number of articles was based on the analysis of similarity to the subject, taking into consideration the aim of the research. Results: After searches, 831 articles have been identified, however, only 25 articles have been chosen for analysis and discussion. Conclusion: Selenium and iodine are essential nutrients for the thyroid gland. Supplementation may improve the functioning of this gland and patients’ life quality, however, more research is needed to expand the knowledge and improve the efficiency of this approach.